Big Book Media: Enhancing Speaking and Listening Skills in Early Childhood Education - Jannah, Miftahul; Muthmainnah, Muthmainnah; Cristianti, Martha; Hayati, Nur (JURNAL PENDIDIKAN USIA DINI, 2025)
The development of speaking and listening skills in early childhood is crucial for cognitive and social growth. Big book media, with its large visualizations and interactive narratives, serves as an effective tool for engaging young learners in language development. This study explores the role of big book media in enhancing speaking and listening skills, identifying both opportunities and challenges in its implementation. Using a Systematic Literature Review (SLR) guided by the PRISMA method, 12 relevant articles published between 2019 and 2024 were analyzed. A qualitative thematic analysis was conducted, applying strict inclusion and exclusion criteria to ensure research alignment. Findings indicate that big book media fosters engagement, encourages participation in discussions, enhances speaking confidence, and improves comprehension through visual storytelling. However, challenges such as insufficient teacher training, a lack of culturally relevant materials, and limited resources restrict its widespread use. In conclusion, while big book media is a valuable tool for early language development, addressing these challenges is essential to maximize its effectiveness in diverse educational settings